Partially replacing synthetic fertilizer with black soldier fly (Hermetia illucens) larvae frass enhances kale (Brassica oleracea var. sabellica) production - Nicholas Romano; Surjya Narayan Datta; Amit Kumar Sinha; Gde Sasmita Julyantoro Pande (Technology in Horticulture)
A by-product of insect farming is 'frass', which is the leftover excrement that can be high in essential minerals. The frass of black soldier fly (Hermetia illucens) larvae (BSFL) is increasingly gaining interest as a soil amendment, but information is limited regarding the feasibility of partially replacing synthetic fertilizers. In this 5-week study, newly-sprouted kale plants were grown with weekly applications of a synthetic fertilizer (control), diluted synthetic fertilizer combined with BSFL frass as a one-time application (½ fert frass) and only BSFL frass as a one-time application (frass). Results showed that the ½ fert frass treatment led to significantly higher biomass of kale than the other treatments, while the stem diameter and height was significantly higher than the control. Potassium and magnesium in kale leaves were significantly lower in the control compared the ½ fert frass treatment while manganese, sodium and zinc were significantly higher in the frass treatment than the control. Iron was significantly highest in the control than the other treatments, but chlorophyll was significantly higher in the ½ fert frass treatment compared to the frass treatment. Among the monosaccharides, mannose was significantly elevated in the leaves of kale grown with only frass. Results indicate that not only can BSFL frass partially replace synthetic fertilizer, but actually showed a growth benefit compared to the sole use of either synthetic fertilizer or BSFL frass.